Keamanan Data Pasien dengan Algoritma Blowfish pada HOTSPODT: Patient Data Security with Blowfish Algorithm on HOTSPODT - Nuniek Fahriani; Indah Kurniawati (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
At HOTSPODT (Hospital Ship for Covid Disaster) there are no stages regarding the application of the use of information technology systems, especially for securing patient data which includes personal data and patient medical records. Confidential patient data collected during the current pandemic, including the patient’s name, address, diagnosis, family history and medical records without the patient’s consent, may pose a risk to the individual concerned. The concept of patient data security is adjusted to the user’s position on the importance of data. Access to patient data authorization is one of the security gaps that the security system needs to pay attention to and guard against. So, in this case applied a data security algorithm in the form of cryptography. The algorithm used is the Blowfish Algorithm. The test results of the scenario in the application prove that it can be successfully processed from the encrypted file to ciphertext until it is returned as the original file.